2019
DOI: 10.3126/saarctb.v17i1.25027
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Drug Resistant Tuberculosis in Samtse General Hospital, Bhutan: A Retrospective Study

Abstract: Introduction: Multidrug resistant tuberculosis (MDR-TB) is defined as a case of tuberculosis resistant to rifampicin and isoniazid which are the first line anti tuberculosis drugs. Globally emergences of MDR-TB possess a challenge to TB control. In Bhutan, the proportion of MDR-TB is high at par with the global level. This study will explore the predictors of MDR-TB and the trend at Samtse General Hospital which has high burden of tuberculosis. Methods: This was a retrospective cross sectional study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Similarly a nationwide study on EPTB in Bhutan showed TSR of 90% [ 8 ]. The lowest TSR for Samtse General Hospital was observed in 2013 which might be due to increased detection of drug resistant TB [ 14 ] after the introduction of liquid culture in Bhutan. The TSR of Samtse General Hospital increased from 83% in 2013 to 89% in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly a nationwide study on EPTB in Bhutan showed TSR of 90% [ 8 ]. The lowest TSR for Samtse General Hospital was observed in 2013 which might be due to increased detection of drug resistant TB [ 14 ] after the introduction of liquid culture in Bhutan. The TSR of Samtse General Hospital increased from 83% in 2013 to 89% in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…In Bhutan, it was found that the mean prevalence rate of MDR-TB was 16%. The burden of primary MDR-TB and secondary MDR-TB is higher in Bhutan (primary 13% and secondary −35%) than other South East Asian countries (Primary −2.7% and secondary −13%) and globally (Primary − 3.5% and secondary 18%) [9] .…”
Section: Introductionmentioning
confidence: 86%